Plotting position for low flow frequency analysis at jempol river streamflow station - Shairul Rohaziawati, Samat; Norasman, Othman (Institute of Physics, 2023)
Low flow frequency analysis is an important technique for calculating the probability of river flow availability during crucial low flow seasons, such as drought. It is also useful to predict the low flow information of a river in volume and frequency for future planning and construction of water resource projects since the low flow has a significant impact on water quality, water supply, and river sustainability conditions. Therefore, this study was performed to determine the low flow frequency analysis of the Jempol River streamflow station using Weibull and Gringorten plotting position formulas. The average recurrence interval (ARI) of 2-, 5-, 10-, 25-, 50-, and 100-year were determined based on 18 years of historical streamflow data. The study illustrates the annual minimum flow magnitude of 1-, 4-, 7-, and 30-day durations for the study area. It shows that the Gringorten formula tends to give higher estimation values up to 18% compared to the Weibull formula when the flow duration increase. Therefore, the outcome of this study could be used in the future for any project related to the low flow information of Jempol River.